1993
DOI: 10.1177/000456329303000603
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ultrafiltrable Copper, Total Copper and Caeruloplasmin Concentrations in Gynaecological Carcinomas

Abstract: Serum copper and caeruloplasmin concentrations are elevated in various carcinomas, but it is not known whether the rise in serum copper is due to elevation of caeruloplasmin alone or whether it is also due to the elevation of ‘free’ copper. We therefore determined ultrafiltrable copper to answer this question. Serum ultrafiltrate was prepared using the Amicon micropartition system and ultrafiltrable (free) copper was determined by flameless atomic absorption spectrophotometry. Serum total copper was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 14 publications
3
29
0
2
Order By: Relevance
“…The mean copper ion concentration for SF was 1.25 + 0.95 × 10 -7 mol.dm -3 (mean + standard deviation) and for RA sera was 2.59 + 1.28 × 10 -7 mol'dm -3. The mean cop- t,er ion concentration for normal control sera was :.45 + 1.62 x 10 -7 mol.dm -3, a value which is comparable to previously reported levels [18] and significantly higher than that ,,f RA serum (P < 0.05) and SF (P < 0.01) (one-way analysis-,,f-variance (ANOVA) performed on untransformed data; fur1her comparisons of sample group means were made using ! 'ukey's test).…”
Section: Resultssupporting
confidence: 87%
“…The mean copper ion concentration for SF was 1.25 + 0.95 × 10 -7 mol.dm -3 (mean + standard deviation) and for RA sera was 2.59 + 1.28 × 10 -7 mol'dm -3. The mean cop- t,er ion concentration for normal control sera was :.45 + 1.62 x 10 -7 mol.dm -3, a value which is comparable to previously reported levels [18] and significantly higher than that ,,f RA serum (P < 0.05) and SF (P < 0.01) (one-way analysis-,,f-variance (ANOVA) performed on untransformed data; fur1her comparisons of sample group means were made using ! 'ukey's test).…”
Section: Resultssupporting
confidence: 87%
“…These free radicals induce mutations by damaging the nucleic acid, DNA. Thus, an increase in serum levels of copper may have a role of compounding factor in case of breast cancer [15]. Like breast cancer, gynaecological cancer has also been found to be directly related to high concentration of copper in blood serum [16].The results of the present study demonstrated increased concentration of Cu for breast cancer patients which support the argument with many of the previous study reported in the literature [12,13,17].…”
Section: Coppersupporting
confidence: 89%
“…A rise in serum ceruloplasmin was observed in cervical cancer (16,17,18). Arumanayagam et al have reported higher levels of ceruloplasmin in later stages of cancer compared to early stages (17).…”
Section: Discussionmentioning
confidence: 98%